Importance of Hearsay in Accordance with the Practice of the European Court of Human Rights - Khidesheli, Tornike (Journal of Law, 2019)
It is obvious, that Article 6 of the European Convention on Human Rights enshrined the principle that before the accused could be convicted all the evidence against him had to be produced in his presence at a public hearing with a view to adversarial argument. In addition the use of statements obtained at the pre-trial stage is not always in itself inconsistent with fair trial right if the defendant has been given an adequate and proper opportunities to challenge depositions at an investigation stage.[1] Perhaps the accused has never had a chance to question witness but it did not automatically result in a breach of fair trial right if there were sufficient counterbalancing factors to compensate for the handicaps under which the defence laboured as a result of limiting witness examination right. Because the defendant faces such kind of handicaps which criminal process law does not include it is necessary to be sufficient counterbalancing factors while using hearsay evidence.Thus, in the present work we will analyze as national courts as European Court of Human Right’s approach to hearsay which enables us to define the purpose of hearsay evidence for criminal process law and master in depth about international court’s experience in the use of hearsay evidence. [1] Windischv. Austria, 1993, ECHR, §26.